Syntheses, crystal structures and applications of novel crystalline metal chalcogenides - Nie, Lina (2017)
Crystalline metal chalcogenides have been a research focus in materials science for a long time due to their abundant structural chemistry and physicochemical properties in the field of photoelectric, ion-exchange, photocatalysis, nonlinear optics, and lithium/sodium-ion batteries (LIBs/SIBs). The chalcogenide chemistry has gained sustainable development by exploring new synthetic methods, designing novel structures and exploiting particular properties. In this dissertation, a series of novel metal chalcogenides have been successfully synthesized through a new synthetic strategy (namely the surfactant-thermal method) and fully characterized. Besides, their semiconductor photocatalytic properties and energy storage performances have been investigated, respectively. Two novel manganese thioantimonates, [MnSb2S4(N2H4)2] (MAS-1) and [Mn(tepa)Sb6S10] (MAS-2), and two new silver thioantimonates, (NH4)AgSb4S7∙H2O (SAS-1) and (NH4)AgSb2S4 (SAS-2), have been prepared and used as efficient photocatalysts for crystal violet (CV) and rhodamine B (RhB) degradation. Two manganese thioantimonates possess neutral layered structure while two silver thioantimonates are constructed with ammonium ions acting as counterions and structure-directing agents. The optical band gaps are estimated to be ~ 1.97 eV for MAS-1, ~ 2.12 eV for MAS-2, ~ 1.70 eV for SAS-1 and ~ 1.85 eV for SAS-2, bespeaking the semiconductor properties for visible light adsorption. Three novel crystalline metal chalcogenides, [NH(CH3)2][Sb4S5(S3)] (ASS), (H3O)2(enH2)Cu8Sn3S12 (CTS) and (NH4)InSb2S5∙phen (IAS), have been explored as anode materials for LIBs/SIBs. Compound ASS is constructed by one dimensional neutral ribbons and dimethylamine molecules are located in interchain space. Single crystal (H3O)2(enH2)Cu8Sn3S12 (CTS) possesses an open framework, in which the interconnected micro-channels (diameter of 1 nm) overall distributed and both of H2en2+ and H3O+ cations located in the micro-channels. ASS and CTS have been explored as electrode materials for LIBs. One attractive feature of (NH4)InSb2S5∙phen (IAS) is that NH4+ ions and phen molecules not only act as counterions but as structure-directing agents or templates. Molecular phen can act as both channels and reservoirs for reversible charging and discharging processes and accommodate the possible volume expansion during cycling. IAS has been explored as an anode material of LIBs and SIBs. In summary, a family of novel crystalline metal chalcogenides have been exploited as photocatalysts for dye degradation and anode materials for LIBs/SIBs.